El arte proletario en cuatro esculturas de Carmen Saco Arenas - Encinas Boyer, Ximena (2024)
This research analyzes the representation of Proletarian art in four sculptures by the Peruvian artist Carmen Saco Arenas (1882-1948). Based on the artist’s statements about her desire to create a Proletarian art, and also on the development and problematics of this artistic movement that arises from the beginning of the Soviet revolution, we seek to understand and explain the aesthetic and contextual conditions in which Saco Arenas produced her sculptural works. In the first place, the life of the sculptress is examined, focusing on her artistic training as well as her political militancy, to then analyze the movement of Proletarian art and its characteristics within the Marxist doctrine. Lastly, we carried out a formal analysis of four sculptural creations by the artist, dated approximately in the third decade of the 20th century. This study also allows us to have some light on how this international movement developed in the local context of the city of Lima at that time. As a result, it is shown that Saco Arenas conceived a particular version of Proletarian art, following the essential values of this avant-garde, but, in turn, framed in the Peruvian context of the early 20th century and influenced by the Indigenism movement.